Resilient Eggs: Highly Successful Loggerhead Sea Turtle Nesting Sites Vary in Their Characteristics - Gravelle, Jessica; Wyneken, Jeanette (Frontiers in Ecology and Evolution, 2022)
Sea turtle nest success, defined as the number of eggs in a nest that successfully hatch and emerge, is closely linked to environmental conditions. Interacting biotic and abiotic factors influence hatching and hatchling emergence success. To date, combinations of multiple factors interacting together, which result in highly successful sea turtle nests are not well understood. Using 25 years of historic nest data and local expert experience, we identified five historically successful loggerhead (Caretta caretta) nesting beaches (hotspots) along the Florida (United States) Atlantic coast and measured nest environments along with the nest success. Principal component analysis was used to reduce 12 environmental variables so that the relative contributions of sand characteristics, nest temperatures, sand moisture, and nest location were considered. The nest environments differed among nesting beaches and were broadly segregated into two distinct climates: subtropical (hot and humid) and warm-temperate (warm and dry). We found that nests at subtropical sites, compared with warm-temperate sites, were characterized by environmental gradients in contrasting ways. Nest locations were predominantly mid-beach in subtropical sites but clustered at higher elevations and closer to the base of the dune at warm-temperate climate sites. Collectively, highly successful nest hotspots represent a mosaic of abiotic factors providing conditions that promote successful hatching and emergence. This new perspective on consistently successful loggerhead nesting beach traits demonstrate that the key traits of sea turtle nesting habitat vary with prevailing climate type and should be managed accordingly.